2014
DOI: 10.4236/ajps.2014.51007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Weather Factors on Seasonal Population Dynamics of <i>Coelaenomenodera elaeidis</i> (Coleoptera: Chrysomelidae) and Its Natural Enemies in NIFOR, Nigeria

Abstract: The leaf miner (Coelaenomenodera elaeidis) is the major pest of the oil palm. Seasonality of C. elaeidis, its natural enemies and their relationship with temperature, rainfall and relative humidity were observed between January 2009 and December 2010 at the main station of the Nigerian Institute for Oil Palm Research. Leaf miner population estimates were obtained from NIFOR entomology division from 1976-1980. This study analyses temporal patterns in leaf miner abundance, and elucidates general patterns and fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…A similar set of microclimatic variables has been associated with Chrysomelidae in other works, specifically temperature, heat index, maximum wind speed and evapotranspiration (Stewart et al 1996;Flinte and Valverde de Macedo 2004;Isard et al 2004;Baselga and Jiménez-Valverde 2007;Linzmeier and Ribeiro-Costa 2013;Aneni et al 2014;Sánchez-Reyes et al 2016b;Oliveira et al 2017;Sandoval-Becerra et al 2017). There are other studies where the most important abiotic variables were solar radiation, precipitation, relative humidity, photoperiod and condensation point (Flinte and Valverde de Macedo 2004;Isard et al 2004;Linzmeier and Ribeiro-Costa 2013).…”
Section: Response Of Chrysomelidae To Seasonal Microclimatic Changesmentioning
confidence: 63%
“…A similar set of microclimatic variables has been associated with Chrysomelidae in other works, specifically temperature, heat index, maximum wind speed and evapotranspiration (Stewart et al 1996;Flinte and Valverde de Macedo 2004;Isard et al 2004;Baselga and Jiménez-Valverde 2007;Linzmeier and Ribeiro-Costa 2013;Aneni et al 2014;Sánchez-Reyes et al 2016b;Oliveira et al 2017;Sandoval-Becerra et al 2017). There are other studies where the most important abiotic variables were solar radiation, precipitation, relative humidity, photoperiod and condensation point (Flinte and Valverde de Macedo 2004;Isard et al 2004;Linzmeier and Ribeiro-Costa 2013).…”
Section: Response Of Chrysomelidae To Seasonal Microclimatic Changesmentioning
confidence: 63%
“…The relationship was slightly positive in both the OPF and SRF, but negative in the UOF. Other studies have also reported significant correlations between beetle diversity and temperature (Pinheiro et al , 2002; Sittichaya et al , 2013; Aneni et al , 2014), for example, Pinheiro and colleagues (2002) showed the abundance of beetles in Brazilian Cerrado was significantly positively correlated with delayed maximum temperature (maximum temperature of the previous month). Most beetles are nocturnal or remain hidden during daylight (when the maximum temperature is most likely to occur), move slowly and rarely fly, and are unlikely to thermoregulate (Lease et al , 2014).…”
Section: Discussionmentioning
confidence: 93%
“…According to Aneni et al. (), higher temperature and lower relative humidity during the dry season increase the incidence of the leafminer Coelaenomenodera elaeidis Maulik, a major pest of oil palm in Africa. Rainfall can also be an important driver of the seasonal dynamics of insect populations.…”
Section: Introductionmentioning
confidence: 99%
“…Souza & Carvalho (2002) reported that the decrease in relative humidity and temperature increased the abundance of Chrysoperla externa (Hagen) in a citrus orchard in southern Brazil. According to Aneni et al (2014), higher temperature and lower relative humidity during the dry season increase the incidence of the leafminer Coelaenomenodera elaeidis Maulik, a major pest of oil palm in Africa. Rainfall can also be an important driver of the seasonal dynamics of insect populations.…”
Section: Introductionmentioning
confidence: 99%